Tibial Eminence Involvement With Tibial Plateau Fracture Predicts Slower Recovery and Worse Postoperative Range of Knee Motion. Issue 7 (July 2017) - Konda, Sanjit R.; Driesman, Adam; Manoli, Arthur; Davidovitch, Roy I.; Egol, Kenneth A.
Abstract : Objectives: To examine 1-year functional and clinical outcomes in patients with tibial plateau fractures with tibial eminence involvement. Design: Retrospective analysis of prospectively collected data. Setting: Academic Medical Center. Patients/Participants: All patients who presented with a tibial plateau fracture (Orthopaedic Trauma Association (OTA) 41-B and 41-C). Intervention: Patients were divided into fractures with a tibial eminence component (+TE) and those without (−TE) cohorts. All patients underwent similar surgical approaches and fixation techniques for fractures. No tibial eminence fractures received fixation specifically. Main Outcome Measurements: Short musculoskeletal functional assessment (SMFA), pain (Visual Analogue Scale), and knee range-of-motion (ROM) were evaluated at 3, 6, and 12 months postoperatively and compared between cohorts. Results: Two hundred ninety-three patients were included for review. Patients with OTA 41-C fractures were more likely to have an associated TE compared with 41-B fractures (63% vs. 28%, P < 0.01). At 3 months postoperatively, the +TE cohort was noted to have worse knee ROM (75.16 ± 51 vs. 86.82 ± 53 degree, P = 0.06). At 6 months, total SMFA and knee ROM was significantly worse in the +TE cohort (29 ± 17 vs. 21 ± 18, P ⩽ 0.01; 115.6 ± 20 vs. 124.1 ± 15, P = 0.01). By 12 months postoperatively, only knee ROM remained significantly worse in the +TE cohort (118.7 ± 15 vs. 126.9 ± 13, P < 0.01). Multivariate analysis revealed that tibial eminence involvement was a significant predictor of ROM at 6 and 12 months and SFMA at 6 months. Body mass index was found to be a significant predictor of ROM and age was a significant predictor of total SMFA at all time points. Conclusion: Knee ROM remains worse throughout the postoperative period in the +TE cohort. Functional outcome improves less rapidly in the +TE cohort but achieves similar results by 1 year. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.